Commensal Bacteria-Dependent CD8αβ+ T Cells in the Intestinal Epithelium Produce Antimicrobial Peptides - Chen, Banru; Ni, Xiang; Sun, Rui; Zeng, Benhua; Wei, Hong; Tian, Zhigang; Wei, Haiming (Frontiers in Immunology, 2018)
The epithelium of the intestine functions as the primary, frontline, physical barrier for protection from enteric microbiota. Intraepithelial lymphocytes (IELs) distributed along the intestinal epithelium are predominantly CD8+ T cells, among which CD8αβ+ IELs are a large population. In this investigation, the proportion and absolute number of CD8αβ+ IELs decreased significantly, in both antibiotic-treated and germ-free mice. Moreover, CD8αβ+ IELs were positively correlated with the diversity of commensal microbes, especially Bacteroidetes and Actinobacteria. Microarray analysis revealed that CD8αβ+ IELs expressed a series of genes encoding potent antimicrobial peptides (AMPs), while CD8αβ+ splenocytes (SPLs) did not. The antimicrobial activity of CD8αβ+ IELs was confirmed by bactericidal assay. In conclusion, microbicidal CD8αβ+ IELs are regulated by commensal bacteria, which in turn, secrete AMPs that play a vital role in maintaining the homeostasis of the small intestine.